2006
DOI: 10.1186/1471-2261-6-44
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial oxidative stress and nitrate tolerance – comparison of nitroglycerin and pentaerithrityl tetranitrate in Mn-SOD+/-mice

Abstract: BackgroundChronic therapy with nitroglycerin (GTN) results in a rapid development of nitrate tolerance which is associated with an increased production of reactive oxygen species (ROS). According to recent studies, mitochondrial ROS formation and oxidative inactivation of the organic nitrate bioactivating enzyme mitochondrial aldehyde dehydrogenase (ALDH-2) play an important role for the development of nitrate and cross-tolerance.MethodsTolerance was induced by infusion of wild type (WT) and heterozygous manga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 50 publications
1
30
0
Order By: Relevance
“…Previous studies have shown that vasorelaxation to PETN is attenuated by pharmacological inhibition or gene deletion of ALDH2 Mollnau et al, 2006;Wenzel et al, 2007a). Although these studies provided circumstantial evidence for a role of ALDH2 in vascular bioactivation of PETN, enzymatic metabolism of the tetranitrate has not been demonstrated so far.…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies have shown that vasorelaxation to PETN is attenuated by pharmacological inhibition or gene deletion of ALDH2 Mollnau et al, 2006;Wenzel et al, 2007a). Although these studies provided circumstantial evidence for a role of ALDH2 in vascular bioactivation of PETN, enzymatic metabolism of the tetranitrate has not been demonstrated so far.…”
Section: Discussionmentioning
confidence: 73%
“…PETN protects against endothelial dysfunction and vascular oxidative stress, largely via HO-1-dependent mechanism. [10][11][12][13][14][15] In this study, we provided novel evidence that upregulation of the antioxidant enzyme HO-1 contributed to PETN-mediated cytoprotective effect by inhibiting mitochondrial ROS generation and NOX4 expression. Previous studies have reported that NOX4-dependent O 2…”
Section: Discussionmentioning
confidence: 86%
“…10,11 PETN has been shown to protect against endothelial dysfunction and vascular oxidative stress. [12][13][14][15] Potential effects of PETN treatment in congestive heart failure (CHF) have not been studied yet. Therefore, we investigated the effects of long-term treatment with PETN on progressive cardiac remodeling (dilation and cellular and molecular dysregulations) in CHF rats after extensive myocardial infarction (MI).…”
mentioning
confidence: 99%
“…Indeed, it is now accepted that polyphenols could prevent many diseases such as cancers (Yang et al, 2009;Korkina et al, 2009;Khan et al, 2009;Bracke et al, 2008;Franklin and McCubrey, 2007), cardiovascular (Madeira et al, 2009;Jones et al, 2011;Kumar et al, 2008;Agouni et al, 2009;Walter et al, 2008;SchiniKerth et al, 2011;Sall Diallo et al, 2008;Sarr et al, 2006 ; and degenerative diseases (Mollnau et al, 2006;Chen et al, 2007;Berrino, 2002;Meydani, 2002;Meydani, 2001). Encouraging the consumption of fruits and vegetables is now a major public health recommendation.…”
Section: Discussionmentioning
confidence: 99%
“…In the current state of knowledge, oxidative stress is a major cause of this phenomenon (Fadel et al, 2012;Oelze et al, 2010;Daiber et al, 2004;Mollnau et al, 2006). Thus, our hypothesis derives from the antioxidant capacity of compounds to reduce or prevent vascular tolerance to nitrates, by reducing oxidative stress.…”
Section: Introductionmentioning
confidence: 99%